4.Oblicz wartość liczbową wyrażenia algebraicznego:
a) 2x – 3xy dla x= -1, y=3
b) (6a+b) – (a – 2b) dla a= -3, b=1
5.Wyłącz wspólny czynnik poza nawias:
a) 4a – 4b=
b) 15xy-25x=
c) – 4xy + 8xyz – 2 xy =
d) 7 x3 y2 z³ – 14 x² y³ z² =

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-03T09:19:57+02:00
4.Oblicz wartość liczbową wyrażenia algebraicznego:
a) 2x – 3xy = 2 * (-1) - 3 * 3 * (-1) = -2 - 9 * (-1) = -2 + 9 = 7
b) (6a+b) – (a – 2b) = 6a + b - a + 2b = 5a + 3b = 5 * (-3) + 3 * 1 = -15 + 3 = -12
5.Wyłącz wspólny czynnik poza nawias:
a) 4a – 4b = 4(a - b)
b) 15xy-25x = 15(xy) - 25y
c) – 4xy + 8xyz – 2 xy = -6(xy) + 8(xyz)
d) 7 x3 y2 z³ – 14 x² y³ z² = 7(x³y²z³) - 14(x²y³z²)
2010-04-03T09:31:41+02:00
4.
a)2x – 3xy=-2 + 9=7
b)(6a+b) – (a – 2b)=(-17) + 1=-16

5.
a) 4a – 4b = 4(a-b)
b) 15xy-25x = 5x(3y - 5)
c) – 4xy + 8xyz – 2 xy = 2xy(-2 + 4z -1)
d) 7 x3 y2 z³ – 14 x² y³ z² = 7x² y² z² (xz - 2y)


na 100% dobrze;)
Pozdrawiam;)
2010-04-03T09:35:55+02:00
4 a
a)2x-3xy=2 x 1 - 3x1x3=2-9=-7
b)(6a+b)-(a-2b)=(6x-3+1)-(-3-2x1)=-18-1=-17--6=11
5
a(4)a-(4)b
b(15)xy-(25)x
c(-4)xy+(8)xy-(2)xy
d(7)x(3) y (2)z3 - (14)x2 y 3 z2